Mseleni joint disease : a study of the clinical and radiological aspects and possible modes of inheritance - Lockitch, Gillian (Social Anthropology, 2017)
Mseleni Joint Disease is a disabling polyarticular disorder occurring with a high prevalence in the Mseleni area of Northern Zululand. During the past three years the series of epidemiological, genealogical and clinico-radiological studies carried out in the Mseleni Joint Disease Project have resulted in: 1. the localisation of a high prevalence area and a neighbouring control or low prevalence area; 2. the identification of individuals affected by the disease and of families consisting of many such individuals; 3. the definition of the clinical and radiological aspects of the disease. The description of these studies forms the subject of this thesis.